Daniel Dodge Brodhead papers - Brodhead, Daniel Dodge
Correspondence, account book, business records, and other papers chiefly relating to Brodhead's work as a U.S. Navy agent in Boston, Mass. Correspondents include John A. Bates, Amos Binney, George H. Brodhead, John Minor Brodhead, John de Bree, William T. Hanes, Gardiner G. Hubbard, Obadiah Huse, William Leverett, Rufus G. Lewis, George W. Pinkerton, Alfred Redington, Alfred Rowe, Charles E. Thompson, and John H. Trowbridge.
U.S. Navy agent and broker. Born 1802.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bates, John A., -- -1871 -- Correspondence; Binney, Amos, -- 1778-1833 -- Correspondence; Brodhead, George H. -- Correspondence; Brodhead, John Minor, -- 1804-1880 -- Correspondence; De Bree, John -- Correspondence; Hanes, William T. -- Correspondence; Hubbard, Gardiner G. -- 1822-1897 -- Correspondence; Huse, Obadiah -- Correspondence; Leverett, William -- Correspondence; Lewis, Rufus G. -- Correspondence; Pinkerton, George W. -- Correspondence; Redington, Alfred -- Correspondence; Rowe, Alfred -- Correspondence; Thompson, Charles E. -- Correspondence; Trowbridge, John H. -- Correspondence; United States. -- Navy -- Supplies and stores; Boston (Mass.) -- Commerce; Brokers; Navy agents